Brand Experience, Perceived Value, and Social Media Marketing to Predicate Brand Loyalty - Cynthia Cynthia; Keni Keni (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to empirically test brand experience, perceived value, and social media marketing to predict brand loyalty in Jakarta. The online questionnaire was distributed using Google Forms with a 5-point Likert scale for each indicator. The number of samples is 185 respondents. All data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) method, using SmartPLS 3.0 software. The results of this study indicate that perceived value and social media marketing can positively predict brand loyalty in Jakarta, but the brand experience cannot positively predict brand loyalty in Jakarta. The results show that brand has not succeeded in carrying out an approach that can influence the moods and emotions of customers that can create a memorable experience for the brand, so loyalty has not yet been created.